Turkey : 2011 Article IV Consultation: Staff Report; Staff Supplements; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation highlights that the Turkish economy continued to grow strongly through the first half of 2011, reaping the benefits of institutional reforms and revamped policy frameworks implemented in the previous decade. However, growth became increasingly fueled by domestic demand and imports. Policy responses were insufficient to prevent the development of a large current account deficit and high inflation. Executive Directors have commended the Turkish authorities for their agile economic management during the global crisis, which, together with structural reforms undertaken earlier, contributed to a rapid recovery.